Calibration of volumetric pipettes using a prototype of a high accuracy pipette calibration set - Wattanahuttakum, Acharawan; Variyart, Weerachai; Limpiyapun, Boontham (Bulletin of Applied Sciences, 2016)
The calibration procedure used to determine the volume of measuring laboratory glassware was generally guided in the international standard. However, a measurement error was possibly occurred if the position of the lowest point of the meniscus was not horizontally tangent to the plane of the upper edge of the graduation line. In this research, a semi-automated pipette calibration set designed and developed by Mass and Volume Laboratory under the Department of Science and Service (DSS) was used for pipette calibration. The use of this prototype device was aimed to reduce the human error from reading meniscus and improve measurement repeatability. Two experiments were investigated. One was to determine the delivery time of pipettes and the other was to measure the actual volume of pipettes at the standard reference temperature of 20°C. The results obtained from using the conventional method and the pipette calibration set were compared. For testing of the delivery time, the results from both manners were almost the same and they were within the limits specified in the international standard. For the volume determination, it was found that the use of the prototype set provided the satisfactory performance as confirmed by the En number less than or equal to 1 (En number ≤1). This value was calculated using the measurement values from the DSS laboratory and the reference value from laboratory accredited by DAkkS and Thailand accreditation body according to ISO/IEC 17025.